Sawahlunto The Cultured City Mine Tour - Darista, Yulid; Dasrizal, Dasrizal; Zuriyani, Elvi (Pendidikan Geografi, 2013)
First coal mine in Sumatra is operated coal mine in Sawahlunto Ombilin in 1892 . But over time , the triumph of coal in Sawahlunto began a drastic decline since the early 2000s . Seeing the condition of depletion of coal since then Sawahlunto city government set its vision as " Sawahlunto 2020 to the Cultured City Mine Tour " . Study was conducted with the aim of 1 ) knowing the attraction which is owned by the city as a tourist Sawahlunto mining cultured 2 ) determine efforts undertaken by the Government to realize Sawahlunto mining cultured tourist town.This study classified as qualitative research , which became key informants in this study is Sawahlunto Mayor , Head Valley Fresh Sawahlunto , PTBA - UPO Sawahlunto , Department of Tourism and Culture Sawahlunto , visitor Â who came to Sawahlunto attractions and traders who are around City attractions Sawahlunto.Informant in this study were taken by purposive sampling technique . Data collection techniques used in this study is the observation , in-depth interviews , and documentation . Data analysis is data reduction , data display, and decision-making and verification.Results of research conducted in the field shows that the conditions that have changed Sawahlunto of City Mine Coal into the mine cultured tourist town so many visitors who come to the attractions in the city as tourist objects Sawahlunto is a former coal mining . So since the depletion of coal Sawahlunto Government and his staff are committed to developing attractions that exist in Sawahlunto Sawahlunto so the main goal of people coming to Sawahlunto .